Implementation of Palembang Mayor Regulation No. 59 of 2011 Concerning Arrangement of Routes in The City of Palembang (Study on Basuki Rahmat and R. Soekamto Street) - Ramuna, Mutiara; Nisyak, Hoirun (HM Publisher, 2019)
The background of this research by still violations freight car or truck against these rules (network traffic) in Jalan Basuki Rahmat and Jl R. Soekamto at hour 6:00 to 9:00 pm. This study aims to determine the implementation Perwali Palembang Number 59 Year 2011 concerning Route Setting of Freight Cars in Palembang. This study uses descriptive qualitative research with descriptive research. The data used are primary data and secondary data. Data was collected through observation, interview and documentation. This study uses the theory of Policy Implementation Ripley and Franklin, where the success of policy implementation is influenced by three dimensions: (1) the level of compliance, (2) a smooth routine functions and (3) the performance and impact of the implementation desired. Based on field research results show for the dimensions of the level of compliance in the implementation of Palembang Perwali still not maximal, fluency routines function has not run smoothly, and the performance and impact of the implementation and the maximum desirable yet not been reached. The conclusion from this study is that the implementation of Perwali Palembang Number 59 Year 2011 concerning Route Settings of Freight Cars in Palembang (Studies in Basuki Rahmat street and R. Soekamto street) have not been successful. This study gives suggestions for traffic rules are adhered to and implemented the network it is necessary to increase the frequency of monitoring and sanctioning the firm.